Open surgical replacement of the descending thoracic and thoracoabdominal aorta in patients with confirmed Marfan and Loeys-Dietz syndromes: A 20-year single-centre experience. (14th March 2022) - Adam, Donald; Iafrancesco, Mauro; Juszczak, Maciej; Claridge, Martin; Quinn, David; Senanayake, Eshan; Clift, Paul; Mascaro, Jorge
Abstract: OBJECTIVES: A relatively small proportion of patients with heritable thoracic aortic disease require open surgical replacement of the distal thoracic aorta. We reviewed the outcome in patients with Marfan and Loeys-Dietz syndromes treated in an aortic centre in the United Kingdom. METHODS: We performed a single-centre retrospective study of consecutive patients treated between October 1999 and December 2019. The primary end point was 30-day mortality. Secondary end points were Kaplan–Meier estimates of medium-term survival and freedom from distal reintervention. Data are presented as median (interquartile range). RESULTS: A total of 58 patients [33 men; 51 with Marfan syndrome; median age 41 years (35–48); median aneurysm diameter 60 mm (55–74)] underwent open descending (n = 21) or thoracoabdominal aortic replacement (n = 37). All repairs were performed using cardiopulmonary bypass with hypothermic circulatory arrest in 31 patients. The 30-day mortality was 5.2% (n = 3, including 2 patients ≥ 60 years with significant comorbidity). Major non-fatal complications included early reoperation (n = 7), tracheostomy (n = 9), temporary renal replacement therapy (n = 3), permanent spinal cord deficit (n = 2) and permanent stroke (n = 1). Median follow-up was 81 months (48–127). Estimated (±standard error) 5-year survival was 85% ±5%. Seven patients had distal aortic reintervention with no deaths or spinal cord deficit: estimated 5-year freedom from distal reintervention was 94% ±3%. There was no difference in survival or freedom from distal reintervention comparing: elective vs. non-elective; type of heritable thoracic aortic disease; DeBakey type; or extent of surgical repair. CONCLUSIONS: Descending thoracic and thoracoabdominal aortic replacement in patients with heritable thoracic aortic disease can be performed with low perioperative morbidity and mortality, satisfactory long-term survival and low requirement for distal reintervention. Abstract : In patients with heritable thoracic aortic disease (HTAD), aortic complications predominantly affect the proximal aorta and a relatively small proportion require intervention on the descending thoracic (DTA) and thoracoabdominal aorta (TAA) [1] for aneurysmal progression of chronic DeBakey type I (after prior proximal aortic surgery) and type III dissections.